Factors affecting dynamics of educability in children and pupils - Valenta, M.; Ludíková, L.; Krejčová, L.; Chrastina, J.; Chráska, M.; Finkova, D.; Langer, J.; Michalík, J. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2016)
The article provides an insight into the processual side and theoretical frame of the research on factors affecting educability and school success/failure in children within a three year long project at Pedagogical Faculty at Palacky University in Olomouc. The first stage focuses on the structure and dynamics of deficits in basic functions in children attending their last year at nursery and first three years of primary school, and on the results of pre research. Статья посвящена первому этапу лонгитюдного теоретико-методологического исследования факторов, благотворно влияющих на обучаемость и школьную успешность, а также факторов, провоцирующих академическую неуспеваемость. Исследование проводилось в течение трех лет на базе педагогического факультета университета Палацкого в Оломоуце. В статье описывается пилотажный этап исследования, целью которого являлись выявление дефицитарных функций, а также оценка их структуры и динамики у дошкольников и младших школьников первых трех лет обучения, имеющих особые образовательные потребности.